A New Approach for the Turbidimetric Determination of Hydronium ion by Using Homemade Linear Array Ayah 5SX1-T-1D-CFI Analyser - M.A. Shakir, Issam; A. Mansoor, Ahmad (Iraqi Journal of Science, 2023)
A new Turbidimetric method characterized by simplicity, accuracy and speed for determination of Hydronium ion by continuous flow injection analysis. The method was based on the formation of complex Zn3[Fe(CN)6] for Zinc(II) that was eluted by Hydronium ion from cation exchanger column with Potassium hexacyanoferrate(III) for the formation of a pale yellow precipitate and this precipitate was determined using homemade Linear Array Ayah-5SX1-T-1D continuous flow injection analyser. The optimum parameters were 2.7 mL.min-1 flow rate using H2O as a carrier stream, 1.7 mL.min-1 reagent stream, 110 L sample volume and open valve for the purge of the sample segment. Data treatment shows that linear range 0.01-0.1 mol.L-1 for each acids (HClO4,HNO3,HCl,H2SO4) while L.O.D 30, 50.01,29.75,51.41 μg/sample for HClO4,H2SO4,HCl,HNO3 respectively from the stepwise dilution for minimum concentration of lowest concentration in linear dynamic range of the calibration graph. The correlation coefficient (r) was 0.9891, 0.9930, 0.9917, 0.9940 while percentage linearity (%r2) was 97.85%, 98.81%, 98.61%, 98.36% for HClO4, H2SO4, HCl, HNO3 respectively. R.S.D. % for the repeatability (n=5) was < 2% for determination of Hydronium ion with concentration 20 and 80 mMol.L-1. The method was applied successfully for the determination of Hydronium ion in commercial samples. Using paired t-test between the newly developed method and classical method; shows that there were no significant differences between either methods. On this basis the new method can be accepted as an alternative analytical method for determination of Hydronium ion in commercial samples.